Bonapartesaurus rionegrensis, a new hadrosaurine dinosaur from South America: implications for phylogenetic and biogeographic relations with North America - Cruzado Caballero, Penélope (2017)
Fil: Cruzado Caballero, Penélope. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina